2022
DOI: 10.1039/d2dt01236g
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient OER catalyst enabled by in situ generated manganese spinel on polyaniline with strong coordination

Abstract: Oxygen evolution reaction (OER), as the rate-determining step of electrochemical water splitting, is extremely crucial, thus it is a requisite to engineer feasible and effective electrocatalysts to shrink the reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Accordingly, the formation of OH* by breaking the strong covalent OH-H bond requires a high energy barrier for initiating the OER process in neutral and acidic environments. [44][45][46][47] The proposed reaction mechanisms are also summarized as follows:…”
Section: Fundamentals Of the Oxygen Evolution Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the formation of OH* by breaking the strong covalent OH-H bond requires a high energy barrier for initiating the OER process in neutral and acidic environments. [44][45][46][47] The proposed reaction mechanisms are also summarized as follows:…”
Section: Fundamentals Of the Oxygen Evolution Reactionmentioning
confidence: 99%
“…Accordingly, the formation of OH* by breaking the strong covalent OH–H bond requires a high energy barrier for initiating the OER process in neutral and acidic environments. 44–47 The proposed reaction mechanisms are also summarized as follows:H 2 O + * → OH ads + H + + e − OH ads → O ads + H + + e − O ads + H 2 O → OOH ads + H + + e − OOH ads → O 2 ads + H + + e − O 2 ads → O 2 + *Overall: 2H 2 O → 4H + + O 2 + 4e − …”
Section: Fundamentals Of the Oxygen Evolution Reactionmentioning
confidence: 99%
“…For example, the use of slender fibers can increase the softness and bending of the textile, while increasing the density of the fiber can increase the strength and stability of the textile. [41,42] In addition, the fabric construction design of a textile also affects its flexible wearable performance. For instance, the use of elastic fibers or the addition of elastic fibers between fibers can increase the elasticity and elasticity of the textile, making it more suitable for body movement and deformation.…”
Section: Structure Designmentioning
confidence: 99%
“…[68][69][70][71] It was demonstrated that the chemical functionalization can effectively modify the electrode/electrolyte interface. [72][73][74] Moreover, surface chemical microenvironment engineering can also induce the electronic effect to not only facilitate the electron transfer but also optimize the binding strength with intermediates. 75,76 Furthermore, the electronic interactions between functional molecules and active species are also beneficial for elevating the electronic conductivity to substantially accelerate the electron transfer.…”
Section: Surface Functionalizationmentioning
confidence: 99%